Behavior of Non-Governmental Organizations in Utilizing the Use of Loan Funds and Revenues of Urban Poverty Reduction Projects (P2KP) - Daswati Daswati; Syahruddin Hattab (Program Pascasarjana Universitas Negeri Makassar, 2018)
The urban poverty reduction project (P2KP), is an institution built by and for the community. The program substantially seeks to reduce poverty through the concept of empowering communities organized in self-help groups. This study aims to analyze and explain the behavior of self-help groups in the utilization of the use of loan funds and income from urban poverty reduction projects (P2KP). The research location was in Palu Timur Subdistrict, Palu City, with descriptive qualitative research. Sources of data obtained from informants with interview, observation and documentation techniques. Informants consist of village heads, BKM, KSM, economic facilitators, community leaders, and target households. The results showed that self-help groups had a lack of effective attachment to the organization (commitment) so that the utilization of revolving funds had not been returned according to the time specified, as evidenced by 87% of the 87 communities involved on time, 16% sometimes on time , 24% that is not timely. Work performance (motivation) varies, there are those who are forced, follow-up and self-awareness, so the revolving way of returning funds varies, because there are still community members who are involved in groups based on forced (5%) or sense of belonging (9%). Steers (1985) argues that it is impossible for an organization to be effective without the sense of attachment and achievement of the workers.